Bond strengths of five tapered root posts regarding the post surface - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2002)
The advantage of tapered passive root posts is their homogenous force transmission without creating stress peaks on the root surface because of their anatomical root form. However, their expected retentive strengths are low compared with the other post systems. The objective of this in vitro study was to determine the retentive strengths of five tapered post systems from different manufacturers using tensile tests. For this purpose, all posts were cemented with zinc phosphate cement (Tenet(R)) into the roots of 50 intact anterior teeth according to the manufacturer's instructions for each system. The contact surface area between the root canal wall and the post was taken into account in the calculations in order to obtain comparable results for different post configurations. The highest bond strength values were achieved for the Erlangen post system(R) (10.8 N mm(-2),) and MP Pirec post system(R) (10 N mm(-2)). These values were more than three times those of the Velva-Post(R) (3.2 N mm(-2)) and the Cylindro-Conical system(R) (3.5 N mm(-2)) and five times more than those of the Dr Mooser post system(R) (1.7 N mm(-2)). The bond strength values of the Erlangen post system(R), Cylindro-Conical system(R) and Dr Mooser post system(R) showed statistically significant differences compared with the other groups. The results of this study indicated that the bond strengths of tapered posts were not only affected by the contact surface but also by the taper angle, shape of the post system, the width of the cement joint, surface roughness of the posts as well as the form of the canal wall. in clinical practice, in case of choosing tapered posts with similar shapes, retention may still vary because of other factors.
Keywords: posts; roughness; bond strength; ENDODONTICALLY TREATED TEETH; RETENTION; RESTORATION; SYSTEMS; TENSILE; DOWELS